2013
DOI: 10.1111/bjh.12516
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to anthracycline‐related congestive heart failure in survivors of haematopoietic cell transplantation

Abstract: Haematopoietic cell transplantation (HCT) survivors are at increased risk for developing congestive heart failure (CHF), primarily due to pre-HCT exposure to anthracyclines. We examined the association between the development of CHF after HCT and polymorphisms in 16 candidate genes involved in anthracycline metabolism, iron homeostasis, anti-oxidant defence, and myocardial remodelling. A nested case-control study design was used. Cases (post-HCT CHF) were identified from 2,950 patients who underwent HCT betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
3
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 45 publications
4
97
3
8
Order By: Relevance
“…Previous pharmacogenetic analyses have reported a protective effect of this SNP, particularly at lower cumulative doxorubicin doses [25,26], or detected no association for this variant with anthracyclineinduced cardiotoxicity [12,27]. Conversely, in our study this variant was more common in patients with systolic dysfunction than in control patients.…”
Section: Resultscontrasting
confidence: 86%
See 3 more Smart Citations
“…Previous pharmacogenetic analyses have reported a protective effect of this SNP, particularly at lower cumulative doxorubicin doses [25,26], or detected no association for this variant with anthracyclineinduced cardiotoxicity [12,27]. Conversely, in our study this variant was more common in patients with systolic dysfunction than in control patients.…”
Section: Resultscontrasting
confidence: 86%
“…If this is a true effect, this silent polymorphism is either tagging a functionally consequential SNP, or this could be another potential example of a synonymous variant that affects protein activity [30]. Risk variants in RAC2 (rs13058338) and NCF4 (rs1883112) were first reported in a large case-control analysis by Wojnowski et al [8] and replicated in independent cohorts [11,12]. Similar to the nominal concordance of the SLC28A3 results, the NCF4 SNP that had been previously reported to increase risk was found more commonly in patients with cardiotoxicity in our cohort, with a slightly lower magnitude of association (1.44 vs 1.88-2.70).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have shown that despite the strong association between certain variables (eg, anthracycline dose, age, hypertension) and post-HCT HF, there is marked inter-individual variability in risk that is not explained exclusively by these factors alone. 29,51,52 For example, susceptibility due to inherited genetic variations in pathways involved in anthracycline-related toxicity have been shown to account for up to 10% of the HF risk after HCT, 38,39 and may need to be accounted for in future risk prediction estimates. As for CAD, the long latency (;10 years) between HCT and CAD may necessitate longer follow-up of our cohort, allowing us to further refine our risk estimates.…”
Section: Discussionmentioning
confidence: 99%